Diseño e implementación del plan piloto de control de acceso aplicando tecnología RFID para Laboratorio 3 Bloque D UPS-SUR - Olivo Barcia, Estefanía Esmeralda (2017)
This technical project was developed at the Universidad Politécnica Salesiana, specifically in Lab 3 of the Campus South Block D, with the purpose of installing a prototype for Access Control using RFID technology, which allows control and registration in an automated way the events of entrance to said physical space. To achieve this purpose, the wireless transmission of data through smart cards based on Radio Frequency Identification (RFID) technology was used to store and retrieve information from several proximity elements such as labels, cards or keyboards, this represents an advantage compared to other technologies such as bar codes, since it eliminates the need to work with line of sight and allows to reprogram the cards even if they are emitting data, the RFID sensor is responsible for reading the labels, sending data with RFID and SPI communication for later encapsulation in Ethernet TCP / IP packets. In addition, a real-time alert system was included by programming an API that can be configured to interact with social networks and by sending emails to the administrator, also offers the possibility of downloading the logs report, to manage security regarding access controls.